A solvent-directed stereoselective and electrocatalytic synthesis of diisoeugenol. Issue 22 (27th February 2018) - Yamamoto, Takashi; Riehl, Barbara; Naba, Keisuke; Nakahara, Kenshin; Wiebe, Anton; Saitoh, Tsuyoshi; Waldvogel, Siegfried R.; Einaga, Yasuaki
Abstract : A stereoselective and electrocatalytic coupling reaction of isoeugenol has been demonstrated for the first time, wherein 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP) plays a crucial role. Abstract : A stereoselective and electrocatalytic coupling reaction of isoeugenol has been reported for the first time in a 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP)/boron-doped diamond (BDD) electrode system. This particular C–C bond formation and diastereoselectivity is driven by a solvate interaction between the radical species and another isoeugenol molecule. Due to an electrocatalytic cycle, only understoichiometric amounts of charge are necessary. Since electric current is directly employed as the oxidant, the reaction is metal and reagent-free. In addition, the electrolysis can be conducted in a very simple undivided beaker-type cell under constant current conditions. Therefore, the protocol is easy to use, suitable for scale-up, and inherently safe.